2016
DOI: 10.1155/2016/1784397
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Papillary Thyroid Microcarcinoma in an Endemic Goiter Area

Abstract: Clinical and pathological characteristics of incidental papillary thyroid microcancer cases, surgical, medical, and nuclear treatment methods, and patients' outcome were studied during follow-up period of 102 months. We studied 37 patients with incidental papillary thyroid microcancer (I-PTM). The surgical procedure was total thyroidectomy in 29 and hemithyroidectomy in 8 patients. Size, multifocality, and bilateralism of PTM foci, thyroid capsule invasion, and presence of lymphovascular invasion were histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Currently, ultrasound is commonly used in the diagnosis of PTC cervical lymph node metastasis[12-14]. The possible ultrasound results including L/S ratio < 2, missing lymphatic portal, liquefaction, calcification and other ultrasound signs suggest lymph node metastasis[15-17]. However, not every patient with lymph node metastasis has typical ultrasound signs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ultrasound is commonly used in the diagnosis of PTC cervical lymph node metastasis[12-14]. The possible ultrasound results including L/S ratio < 2, missing lymphatic portal, liquefaction, calcification and other ultrasound signs suggest lymph node metastasis[15-17]. However, not every patient with lymph node metastasis has typical ultrasound signs.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid lesions are not only a sign of the expression of a single disease but are the clinical manifestation of a wide range of different diseases [ 3 ]. Goitrous thyroid lesion is postulated as a precursor lesion to thyroid carcinoma, because in many parts of the world, endemic goiter is a major concern [ 4 ]. It is also well understood that the occurrence of thyroid lesions will increase with iodine deficiency [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other common complications of thyroid are Graves’ disease, Hashimoto’s thyroiditis, adenoma, thyroid carcinoma, hypothyroidism, and hyperthyroidism, which are the prevalent types of thyroid disorders [ 6 , 7 ]. Several previous studies have reported that the prevalence of goiter varies according to the geographical region, age, and sex [ 4 , 6 - 8 ]. The incidence of thyroid lesion increases with age, after radiation exposure, and women are 10 times more likely than men to have thyroid problems.…”
Section: Introductionmentioning
confidence: 99%
“…Female preponderance is seen in both incidental and nonincidental Pm. (3,14,18) However, no difference is noted in the incidental and non-incidental group. This is in comparison with study of Provenzale et al (3) The mean age at presentation for incidental and nonincidental Pm (Table 1) is comparable and is not significantly different.…”
Section: Discussionmentioning
confidence: 85%
“…Incidental Pm has been associated with Multinodular/ endemic goitre, and increased levels of Thyroid Stimulating Hormone. (3,10,11,12,13,14) Many researchers correlate the incidental Pm with the variable use of ultrasonography and ultrasound guided needle aspiration. Regardless of the pre -operative diagnostic method, cases of Pm are detected incidentally post-operatively in many instances.…”
Section: Discussionmentioning
confidence: 99%